Thyroid Carcinoma in Nigeria: Current Perspectives and Comprehensive Review - (:unkn) unknown (My University, 2025)
Background: Malignant thyroid disease is an emerging yet underreported public health issue in Nigeria and Sub-Saharan Africa. Although generally associated with a favourable prognosis when detected early, substantial gaps in diagnosis, treatment, and data reporting hinder optimal care in the region.Objective: To provide a comprehensive evaluation of the current state of malignant thyroid disease in Nigeria, focusing on diagnostic patterns, treatment challenges, and opportunities for systemic healthcare improvements.Methods: A narrative review of peer-reviewed literature from the past two decades was conducted, incorporating global, Sub-Saharan African, and Nigerian studies. The review examined histopathological trends, diagnostic infrastructure, access to therapy, and policy gaps in thyroid cancer management.Findings: The review highlights significant systemic deficiencies, including poor cancer registration systems, limited correlation between cytology and histology, inadequate molecular diagnostic capabilities, and restricted access to radioactive iodine therapy. These barriers contribute to delayed diagnoses, outdated treatment protocols, and poor outcomes. Comparative analysis indicates that Nigeria lags behind both regional and global standards of thyroid cancer care.Conclusion: To improve thyroid cancer outcomes in Nigeria, urgent investments are needed in cancer registries, diagnostic infrastructure, workforce training, and nuclear medicine. Integrating thyroid cancer services into national health insurance and adopting context-specific clinical guidelines are critical steps toward aligning with global best practices.
Keywords: African Research